(untitled) (Physical Education, Health and Social Sciences, 2026)
Polycystic ovary syndrome (PCOS) is a complex metabolic-endocrine disorder characterized by insulin resistance, hyperandrogenism, and ovulatory dysfunction. This study evaluated the effects of Cinnamomum zeylanicum and inositol, individually and in combination, on metabolic and hormonal parameters in overweight women with PCOS. Cinnamon bark powder was analyzed for proximate composition and antioxidant activity using total phenolic content (TPC), DPPH, and FRAPS assays. A 12-week randomized, double-blind, placebo-controlled trial was conducted in 28 women with PCOS (n = 7 per group). Participants received cinnamon (1.5 g/day), inositol (2,200 mg myo-inositol + 55 mg D-chiro-inositol/day), their combination, or placebo. Primary outcomes included fasting glucose, luteinizing hormone (LH), testosterone, and ovarian morphology, while secondary outcomes were FSH, TSH, and prolactin. Cinnamon showed high dietary fiber (30.4%) and strong antioxidant activity. Clinically, the combination treatment produced the most significant improvements (p < 0.05), reducing LH (10.4%), testosterone (11.17%), fasting glucose (14.37%), and ovarian ultrasound scores (30.03%). Cinnamon alone improved FSH and glycemic parameters, whereas inositol mainly improved LH, testosterone, and glucose levels. Combined supplementation demonstrated superior metabolic and endocrine benefits, suggesting a synergistic nutraceutical approach for PCOS management.